2014
DOI: 10.5713/ajas.2013.13670
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Lactic Acid Bacteria Isolated from Tomato Pomace Silage

Abstract: Silage making has become a significant method of forage conservation worldwide. To determine how tomato pomace (TP) may be used effectively as animal feed, it was ensilaged for 90 days and microbiology counts, fermentation characteristics and chemical composition of tomato pomace silage (TPS) were evaluated at the 30th, 60th, and 90th days, respectively. In addition, 103 lactic acid bacteria were isolated from TPS. Based on the phenotypic and chemotaxonomic characteristics, 16S rDNA sequence and carbohydrate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
(38 reference statements)
1
10
2
Order By: Relevance
“…This difference is thought to be caused by losses in the form of silo effluents. The DM values of the silages obtained from the our study was lower (23.04-34.64%) than the values obtained in other studies (Weiss et al, 1997;Di Blasi et al, 1997;Çapçı et al, 2002;Denek and Can, 2006;Mirzaei et al, 2008;Orosz et al, 2012;Mendez-Llorente et al, 2014;Wu et al, 2014). These differences in DM contents of tomato pomace may be associated with the differences in production technologies implemented during the process of producing tomato pomace (Denek and Can, 2006).…”
Section: Discussioncontrasting
confidence: 66%
“…This difference is thought to be caused by losses in the form of silo effluents. The DM values of the silages obtained from the our study was lower (23.04-34.64%) than the values obtained in other studies (Weiss et al, 1997;Di Blasi et al, 1997;Çapçı et al, 2002;Denek and Can, 2006;Mirzaei et al, 2008;Orosz et al, 2012;Mendez-Llorente et al, 2014;Wu et al, 2014). These differences in DM contents of tomato pomace may be associated with the differences in production technologies implemented during the process of producing tomato pomace (Denek and Can, 2006).…”
Section: Discussioncontrasting
confidence: 66%
“…helveticus, but a study of lactic acid bacteria diversity in tomato pomace silage reported that 4% of the isolates belonged to Lb. helveticus [41], which suggests this species is part of the common lactic bacteria community. However, direct inoculation of wilted rice straw with a Lb.…”
Section: Eubacterial Succession Over the Incubation Periodmentioning
confidence: 93%
“…amylovorus strain that was isolated. 23,39,40) The LAB species secretes amylase into the culture broth, suggesting that the LAB species may be useful for making silage. In fact, the PY45 strain that we have identified as Lb.…”
Section: Discussionmentioning
confidence: 99%